2019
DOI: 10.1007/s11769-019-1024-4
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Offsetting in China’s Coastal Wetlands: Existing Challenges and Strategies for Future Improvement

Abstract: Land-use changes in coastal wetlands have led to a worldwide degradation of marine coastal ecosystems and a loss of the ecological services they provide. Ecological offsetting is a popular strategy and an effective mitigation measure for ecosystems that have been degraded, damaged, or destroyed and is critical for habitats where natural recovery is hindered. However, the current understanding of the theory and practice of ecological offsetting for coastal wetlands is extremely limited in many developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…These studies have revealed significant disparities in the level of high-quality development of the marine economy among coastal regions. Scholars have also explored paths for achieving high-quality development from various perspectives, including ecological environmental protection [11], national security strategies [12], building a modern marine industry system [13,14], optimizing spatial layout [15], and enhancing efficiency through factors such as technology [16], funds [17], and policies [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed significant disparities in the level of high-quality development of the marine economy among coastal regions. Scholars have also explored paths for achieving high-quality development from various perspectives, including ecological environmental protection [11], national security strategies [12], building a modern marine industry system [13,14], optimizing spatial layout [15], and enhancing efficiency through factors such as technology [16], funds [17], and policies [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…China has a vast coastal area throughout its coastline. The coastal wetlands play an important role in protection of critical habitat, degradation of pollutants, maintenance of regional of ecological balance, and promotion of the economic growth (He et al, 2014;Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%